A Case Report: Genetically Distinct Severe Acute Respiratory Syndrome Coronavirus-2 Variant Causing Reinfection - Hossain, Mohammad Enayet; Rahman, Md. Mahfuzur; Alam, Md. Shaheen; Sarmin, Monira; Karim, Yeasir; Hasan, Mehedi; Hoque, Ananya Ferdous; Hasan, Md. Mahmudul; Rahman, Mohammed Ziaur; Chisti, Mohammod Jobayer; Rahman, Mustafizur (Frontiers in Microbiology, 2021)
Background. Emergence of the novel variants has been a great deal of international concern since the recently published data suggest that previous infections with SARS-CoV-2 may not protect an individual from new variants. We report a patient had two distinct episodes of COVID-19 with different variants of SARS-CoV-2. Methods. The nasopharyngeal samples collected from the two episodes were subjected to whole genome sequencing and comparative genome analysis. Results. The first infection presented with mild symptoms, while the second infection with severe outcomes which occurred 74 days after the patient recovered from first episode. He had elevated C-reactive protein, ferritin and bilateral consolidation as a sign of acute infection. Genome analysis revealed that the strains from the first and second episodes belonged to two distinct Nexstrain clades 20B and 20I and Pangolin lineages B.1.1.25 and B.1.1.7, respectively. A total of 36 mutations were observed in the episode-2 strain when compared with the reference strain Wuhan-Hu-1. Among them, 8 mutations were identified in the receptor binding domain (RBD). Conclusions. Our findings concern whether the immunity acquired by natural infection or mass vaccination could confer adequate protection against the constant evolving SARS‐CoV‐2. Therefore, continuous monitoring of genetic variations of SARS‐CoV‐2 strains is crucial for interventions such as vaccine and drug designs, treatment using monoclonal antibodies, and patient management.